UPAYA MENINGKATKAN KEMAMPUAN SISWA DALAM MENULIS TEKS ILMIAH FAKTUAL (FACTUAL REPORT) MELALUI MODEL PEMBELAJARAN DISCOVERY LEARNING (Penelitian Tindakan Kelas pada Pembelajaran Bahasa Inggris di Kelas XI IPS-3 SMA Negeri 1 Sariwangi) - Yayan Sutaryanto (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2022)
The reality in Class XI IPS-3 SMA Negeri 1 Sariwangi, students have difficulty in writing factual scientific texts (factual report). The difficulties in writing factual scientific texts (factual reports) include determining the main ideas (ideas) and compiling a writing framework based on the aims and objectives, as well as the audience of readers, copying the main ideas according to the writing framework in the form of written language, perfecting the writing from the linguistic aspect, word use and spelling. Thus, to overcome students' difficulties in writing factual scientific texts (factual reports) we need a way to make it easier for students to describe the actual situation through words. One alternative way of writing factual scientific texts (factual report) is through the Discovery Learning Learning Model. The media that is expected to help teachers convey and facilitate the delivery of English learning concepts to improve the ability to write factual scientific texts (factual reports) is through the Discovery Learning Learning Model.The general objective of this research is to find out the data on increasing students' ability to write factual scientific texts (factual reports) through the Discovery Learning Learning Model in learning English in Class XI IPS-3 SMA Negeri 1 Sariwangi.The method that will be used in the research is Kemmis and Taggart's Class Action Research (CAR). The considerations that underlie this research method, because the research steps are quite simple, so they are easily understood and implemented by researchers.Student learning outcomes about students' ability to write factual scientific texts (factual report) through the Discovery Learning Model have an effect on increasing student learning outcomes. The ability of students to write factual scientific texts (factual report) after using the Discovery Learning Learning Model in learning English language and literature in Class XI IPS-3 SMA Negeri 1 Sariwangi proved to have increased, namely student learning outcomes in the first cycle, namely 75% increased to 83% in the first cycle. II.